External control of fluoridation in the public water supplies of Brazilian cities as a strategy against caries: a systematic review and meta-analysis - Bárbara Souza Martins Rosário; Henrique Damian Rosário; Walbert de Andrade Vieira; Graziela Oro Cericato; Diego Figueiredo Nóbrega; Cauane Blumenberg; Fernando Neves Hugo; Márcio Magno Costa; Luiz Renato Paranhos (BMC, 2021)
Abstract Background Among the methods currently available to provide fluoride in population levels, fluoridated water is the most successful for presenting high efficacy, safety and good cost-benefit. However, recent studies on external control have shown great variability of fluoride concentrations in the water from treatment stations in Brazilian cities, which must present concentration between 0.6 and 0.8 mg/L to be considered acceptable in most cities. Thus, this study aimed to perform a systematic review of the literature to assess the adequacy of fluoride concentration in the water in Brazilian cities using external control. Methods The protocol was registered in PROSPERO. Six databases were used as primary search sources and three databases were used to partially capture the "gray literature". Only observational studies that assessed the fluoride concentration of artificially fluoridated water from the public supply network were included. The JBI Critical Appraisal Tools for Systematic Reviews was used to assess the risk of bias of the studies. A proportion meta-analyses using random-effect models were performed. The heterogeneity between studies was determined by I2 statistic. Meta-regressions were conducted to identify relevant moderators to be used in stratified meta-analyses. Publication bias was investigated by Egger's tests. Results The search provided 2038 results, from which 14 met the eligibility criteria and were included in the data extraction of the review. Overall, the water samples were collected from 449 different sources in three Brazilian regions. Thirteen studies presented a low risk of bias. The mean concentration of fluoride ranged from 0.17 to 0.89 ppmF. The meta-analyis demonstrated that more than half of the water samples analyzed had fluoride concentration levels outside the acceptable range (56.6%; 95% CI 45.5; 67.3), with high heterogeneity. Conclusion More than half of the public water supply analyzed in the studies selected had fluoride concentration levels outside the acceptable range, which may affect the risk of developing oral diseases in the Brazilian population, having an important impact on public health.